The impact of the underpinnings of relationship marketing on customer loyalty in Telekom Malaysia / Nurfadhilah Basri - Basri, Nurfadhilah (Faculty of Business and Management, 2008)
The development of effective customer relationships is increasingly recognized as an important component of marketing strategies. The purpose of this research is to examine the impact of relationship marketing underpinnings namely, trust, commitment, communication and conflict handling on the quality of firm-customer relationship as well as the levels of contribution of these underpinnings on customer loyalty in Telekom. For the purpose of this research, the descriptive research was used 60 questionnaires were distributed to customers of TM Bukit Raja Klang, and collected using nonprobability sampling technique. Questionnaires were distributed as the survey instrument as the source of primary data, other reliable resources would serve as secondary data. The statistical package for the social science (spss) version 11.0 has been used to summarize the data. The results are in the form of reliability testing, frequency, descriptive and correlation. Based on this research, the results support most of the hypothesized relationships. There is a signiftcant positive relationship between trust, commitment, communication and conflict handling on customer loyalty.